Polymerization of resin composite restorative materials: exposure reciprocity - Musanje, L.; Darvell, B.W. (Dental Materials, 2003)
To examine whether there is reciprocity between irradiation time and irradiance with regard to the mechanical properties of filled, resin composite restorative materials (RCs). Four visible light-cured RCs, all of shade A3, were used: Heliomolar Radiopaque (HR) and Tetric Ceram (TC) (Ivoclar, Schaan, Liechtenstein), Filtek Z250 (FZ) (3M, St Paul, MN, USA) and Prodigy condensable (PR) (Kerr, Orange, CA, USA). Bar specimens (1.0×1.5×16.0 mm3) were cured at irradiances (I) ranging from 25–1500 mW/cm2 and irradiation times (t) of 1–3000 s. Six specimens at 250 combinations of t and I were prepared and stored in artificial saliva of pH 6, at 37 °C for 7d before performing three-point bend tests for flexural strength (F), flexural modulus (E) and total energy to failure (W). Contour plots of property value vs. t and I on log scales were prepared. Results. The contour plots showed three regions: unset at low I·t, a plateau corresponding to more or less full property development, and connecting ramp. The boundary between the plateau and the ramp suggests the minimum acceptable exposure. No practical lower limit to irradiance was detected, but there may be no benefit from increasing I beyond about 1000 mW/cm2. The slopes of the contours in the log–log plots provided a test of the hypothesis of reciprocity. These slopes were ∼−1.5 for HR, TC and PR; and ∼−1 for FZ, compared with the expected value of −1. The general hypothesis therefore fails. The existence of localized maxima in property values is further evidence of that failure, even for FZ. Significance. Dentists may use any lamp, including LED sources, and attain satisfactory results providing irradiation time is long enough. Manufacturers ought to supply a graph indicating the minimum acceptable exposure for each product for specified curing lamps. Calculations based on total energy delivered to guide irradiation protocols are invalid and do not recognize product behavior.
Keywords: Modulus of elasticity; Filled resin composite restorative materials; Irradiance; Irradiation time